DEVELOPING TOURISM VILLAGE FROM ARTS AND THE CITIZENS’ ACTIVITIES (CASE OF DAGO POJOK, BANDUNG, INDONESIA) - Adiati, Gracia (PEOPLE: International Journal of Social Sciences, 2016)
Dago Pojok is an area located on Dago Pojok Street, Coblong district, Bandung, West Java. In this area, there is a village which is full of arts both the decoration and the citizens‟ activities. Because of its unique, this village is called “Kampung Kreatif Dago Pojok”. In the past, this village was one of a troubled region because of motorcycle gang existed there. In 2003, a community called Taboo Community came to Dago Pojok for making art training to its citizens. The arts are mural, painting, wall decoration, statue, photography, traditional music instruments, and traditional games. In making this paper, the data are collected by interview to the initiator of “Kampung Kreatif Dago Pojok” direct observation, and studies from articles in several media. The data were analyzed by referring to the theories of innovation diffusion, social exchange, social learning, and organizational communication. “Kampung Kreatif Dago Pojok” has already successfully in changing, from a troubled area became a tourism destination that still in development in Bandung. Many tourists, both domestic and foreign come to see the unique of this village, participate in arts programs and stay in citizens‟ house. These activities support the citizens to start a business and grow in economics. This paper discusses how „Kampung Kreatif Dago Pojok‟ has developed by its creativity. This paper also explain Taboo community profile, the activities of Dago Pojok, Kampung Kreatif Dago Pojok development, innovation diffusion process, social exchange and social learning process, community based tourism in Dago Pojok, and Dago Pojok programs. The explanation will reveal how communication between the citizens, organizers of “Kampung Kreatif Dago Pojok”, and Taboo Community became a key factor that made the village people understand the importance of area developing, so Dago Pojok which was a common village became a creative village that get a lot of attention.